An evaluation of weaning strategies for Great Plains cow-calf producers - Bailey, Eric Arthur (Kansas State University, 2013)
We evaluated effects of preconditioning on performance and health of beef calves raised and finished in the Great Plains. In experiment 1, calves were preconditioned for 0, 15, or 45 d and vaccinated against BRD-causing pathogens 14 d before maternal separation or after feedlot arrival. During receiving and finishing, preconditioned calves had greater DMI and ADG than non-preconditioned calves; however, timing of BRD vaccination did not affect animal health. In experiment 2, calves were vaccinated against BRD pathogens 0, 1, 2, or 3 times during a 30-d preconditioning program. Vaccination for BRD, regardless of degree, improved health during preconditioning; however, DMI, ADG, and G:F during preconditioning, receiving, and finishing were unaffected by degree of vaccination. In experiment 3, calves were preconditioned for 30 d, shipped 4 h to an auction facility, commingled for 12 h, and transported 4, 8, or 12 h to a feedlot. Feedlot performance and health of beef calves were not affected by transport of up to 12 h following auction-market commingling. In experiment 4, beef calves were subjected to 1 of 3 ranch-of-origin preconditioning programs: drylot weaning + abrupt dam separation, pasture weaning + fence-line contact with dams, and pasture weaning + fence-line contact with dams + supplemental feed delivered in a bunk. Drylot-weaned calves gained more weight during preconditioning. Unsupplemented, pasture-weaned calves had the least ADG during receiving but had greater ADG during finishing and had carcass characteristics similar to other treatments. In experiment 5, we evaluated performance of early-weaned beef calves fed grain-based diets with DMI adjusted to achieve ADG of 0.45, 0.91, or 1.36 kg/d during an 84-d growing period. Calves fed at restricted rates did not exhibit improved G:F relative to full-fed counterparts. In addition, there appeared to be limitations associated with predicting DMI and ADG of light-weight, early-weaned calves fed a grain-based diet.
Keywords: Beef Cattle; Weaning; Preconditioning; Health; Animal Sciences (0475)